1998
DOI: 10.1088/0022-3727/31/23/001
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of thin silver film grown by dc sputtering on Si(001)

Abstract: The morphology and growth mechanism of silver films approximately 150Å in thickness on Si(001) substrates have been studied by atomic force microscopy and x-ray reflectivity. The thin films prepared by dc sputtering at room temperature are composed of islands of silver. The shape and size distribution of these islands are studied using these two complementary measurement techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(42 citation statements)
references
References 20 publications
4
34
0
2
Order By: Relevance
“…Figure 3 shows AFM images of CdTe thin films deposited at different deposition times. The films surface are formed by small rounded grains; observed for most of the sputtered materials [21,22]. The roughness of the films deposited at different deposition times are given in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3 shows AFM images of CdTe thin films deposited at different deposition times. The films surface are formed by small rounded grains; observed for most of the sputtered materials [21,22]. The roughness of the films deposited at different deposition times are given in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Yang et al [13] demonstrated that the bimetal Ag-Au NPs far more stable than the pure Ag NPs against oxidation. Ag NPs are prepared by various wet chemistry methods [14,15], vacuum deposition techniques (VDT) which includes thermal evaporation [16], sputtering [17] and pulsed laser deposition [18] etc. Amongst, VDT is advantageous over wet chemistry routes because it can directly be used for the above mentioned applications before going for any surplus process.…”
Section: Introductionmentioning
confidence: 99%
“…The results clearly indicate the formation of ellipsoidal islands. The morphology of these islands could be extracted from these complementary measurements [36]. STS measurements of these islands having different density profiles show the opening of a "band-gap" in the Au clusters as cluster-size is reduced [37].…”
Section: Metal Filmsmentioning
confidence: 99%
“…These studies are important to understand not only the growth mechanisms [17,20,24,28,36,42,45] of these materials but also the unusual properties of nanomaterials such as continuous melting process [19,64,65], negative thermal expansion [66], and semiconductorlike transport properties of metals [2,35,37,38].…”
Section: Nanocomposite Filmsmentioning
confidence: 99%